Health Equity through Structural Adjustment by Nepal for Public Health - Bhurtel, Khem Kumar; Basnet, Parmila; Sigdel, Shalikram; Magar, Keshar Jung; Ghimire, Sita Ram; Paudel, Ganga Ram (Orchid Academia Siraha, 2023)
The study states at Nepal's healthcare system, emphasizing structural changes and obstacles to enhanced health of people. The federal system prioritizes social determinants, healthcare personnel, quality access, community involvement, and the impact of globalization on health while providing comprehensive services despite decentralization and collaboration. With an emphasis on social justice and the promotion of public health, this paper investigates Nepal's healthcare system and health equity in the context of globalization. Reviewing data, policy, implementation, and literature assists it to analyze and draw conclusion. In discussing Nepal's shift from a unitary to a three-level federal government structure, the article highlights the consequence of developing policies and programs that promote social justice and equity in health. In addition to calling for a massive effort by the public health community to discuss and analyze health crises related to globalization and develop social justice-based strategies for a world where health for all is a reality, it suggests that a single strategy should be developed to address health crises.